Beneficios del biol en el cultivo de pepino (Cucumis sativus) - Muñiz Veliz, Carlos Alfredo (2023)
This document detailed the benefits of biol in the cultivation of cucumber (Cucumis sativus). Cucumber is an important vegetable in family farming systems and has very particular characteristics. Some of the alternatives for sustainable crop production are organic fertilizers. The conclusions determined that biol is a phytoregulatory organic source that is capable of promoting physiological activities and stimulating plant development, influencing agronomic activities such as: rooting (increases and favors the root base), action on the foliage (extends the foliar base), improves flowering and activates the vigor and germination power of the seeds, all of which translates into a significant increase in cucumber yields; It is an organic fertilizer in cucumber cultivation, it is applied in amounts greater than 15 L/ha; these can be in high dose (135 L/ha), medium (90 L/ha) or low (45 L/ha); The quality of the biol depends on the composition, being the most used manure and green matter, since it is easily assimilated according to the conditions of the crop and the variety to be used and the biol contributes to the cucumber crop with vitamins, amino acids and nutrients such as Nitrogen, Phosphorus, Potassium, Magnesium, Calcium, Sodium, Nickel and Zinc, highly available and assimilable for the proper development and growth of plants.